2002
DOI: 10.1046/j.1365-313x.2002.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative burst involved in apoptotic response in oats

Abstract: SummaryApoptotic cell response in oats is induced by victorin, a host-selective toxin secreted by Cochliobolus victoriae and thought to exert toxicity by inhibiting mitochondrial glycine decarboxylase (GDC) in Pc-2/ Vb oats. We examined the role of mitochondria, especially the organelle-derived production of reactive oxygen species (ROS), in the induction of apoptotic cell death. Cyto¯uorimetric analysis showed that victorin caused mitochondrial DY m breakdown and mitochondrial oxidative burst. Ultrastructural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 71 publications
10
122
0
1
Order By: Relevance
“…Plant mitochondrial responses to PCD signals are similar to those of animal mitochondria and include undergoing a permeability transition, release of cytochrome c, and a decrease in ATP production (Xie and Chen, 2000;Arpagaus et al, 2002;Tiwari et al, 2002;Krause and Durner, 2004). Increases in mtROS production are coincident with these processes, probably a result of the large perturbations experienced by the mtETC (Pellinen et al, 1999;Yao et al, 2002;Krause and Durner, 2004).…”
Section: Pcd and Response To Pathogensmentioning
confidence: 98%
See 3 more Smart Citations
“…Plant mitochondrial responses to PCD signals are similar to those of animal mitochondria and include undergoing a permeability transition, release of cytochrome c, and a decrease in ATP production (Xie and Chen, 2000;Arpagaus et al, 2002;Tiwari et al, 2002;Krause and Durner, 2004). Increases in mtROS production are coincident with these processes, probably a result of the large perturbations experienced by the mtETC (Pellinen et al, 1999;Yao et al, 2002;Krause and Durner, 2004).…”
Section: Pcd and Response To Pathogensmentioning
confidence: 98%
“…Mitochondria in situ show the same effect. Studies using whole cells have shown increased ROS production specifically from mitochondria in the presence of the cytochrome pathway inhibitor antimycin A (AA; Maxwell et al, 1999;Yao et al, 2002).…”
Section: Generation Of Mtrosmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of this exists within theintrinsic pathway of cell death that has been observed to contribute to programmed cell death in yeasts, 26 humans 27 and plants. [28][29][30] During apoptosis driven by the intrinsic pathway, permeabilization of the mitochondrial outer membrane leads to the release of pro-apoptotic, factors such as cytochrome c, apoptosis-inducing factor 1 (AIF1) and Figure 1 The F-actin cytoskeleton of S. cerevisiae. A dividing S. cerevisiae cell stained with Alex488-Phalloidin, which binds specifically to F-actin-containing structures, is shown.…”
Section: Yeast and The Intrinsic Pathway Of Apoptosismentioning
confidence: 99%